Lower desorption temperature in CO2 capture using various magnesium oxide loading on iron(III) oxide by ultrasonic-assisted synthesis: the adsorption-desorption and isotherm studies - Lahuri, Azizul Hakim; Jaafar, Nur Farhana; Nordin, Norazzizi; Dzakaria, Norliza; Mohd Yusof, Syawal; Samidin, Salma; Sulaiman, Syazreen Nadia; Marliza, Tengku Sharifah (Taylor and Francis Ltd., 2024)
This study introduces a novel approach to CO2 capture using the ultrasonic-assisted wet impregnation technique with various MgO loadings on Fe2O3. This method allows for enhanced dispersion of MgO particles, leading to improved adsorption and desorption characteristics. The characterization was conducted using XRD, N2 adsorption-desorption isotherms and FESEM. CO2 adsorption isotherm at 25 °C and TPD-CO2 were applied to obtain the CO2 capture activities. The linearized form of adsorption isotherm model was fitted to the experimental data from the CO2 adsorption isotherm at 25 °C. The most effective adsorbent is 20MgO/Fe2O3 with 20 wt% dopant loading which has an adsorption capacity of 3.83 and 56.99 mg/g for physisorption and chemisorption, respectively. It has the highest pore size distribution at 80–150 nm among MgO/Fe2O3 series adsorbents. This discrepancy is ascribed to a good distribution of the MgO particle on the Fe2O3 surfaces and the pores generated on the MgO surfaces. XRD revealed a greater peak shift to a higher angle of 2θ for the (104) plane starting from 20MgO/Fe2O3. This shows that the Fe3+ ion in the Fe2O3 structure has been successfully replaced by a smaller ion radius of Mg2+ and the ion was successfully incorporated into the Fe2O3 as a substitutional atom. The Freundlich isotherm model fit the best with the experimental data suggesting that the heterogeneity surface facilitated a successful multilayer adsorption process. The novelty of this work lies in the ability to enhance CO2 adsorption efficiency while lowering the desorption temperature, offering a practical CO2 capture applications.